Love and the practice of innovation!: Roles of entrepreneurial passion and perceived innovation importance in the practice-innovation link - Shichao Yu; Arslan Ayub; Hasnain Bashir (Journal of Innovation & Knowledge (JIK), 2024)
In organizations, the success of innovation efforts in improving performance relies heavily on entrepreneurial passion and the perceived importance of innovation. Understanding the link between deliberate practice and innovation broadens our current knowledge, emphasizing entrepreneurial passion as a driving force and the perceived importance of innovation as a crucial amplifying factor for performance. This study posits that deliberate innovation practice enhances innovation performance by fostering entrepreneurial passion, which is further influenced by the perceived importance of innovation. Grounded in self-determination theory and social cognition theory, this research collected data through a multisource, three-wave approach from software company employees. Utilizing SmartPLS (v 4.0) for measurement and structural model evaluation, the findings reveal that deliberate innovation practice positively impacts innovation performance. Entrepreneurial passion serves as a mediator between deliberate innovation practice and innovation performance, with perceived innovation importance strengthening this effect. This study demonstrates that the impact of deliberate innovation practice on performance is more pronounced when entrepreneurial passion mediates, especially at higher levels of perceived innovation importance. The findings offer essential theoretical insights and practical implications.
Keywords: L26; O31; 650; Deliberate innovation practice; Entrepreneurial passion; Innovation performance; Perceived innovation importance